(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The recent climate of competition has led to the emergence of sizable rent-seeking professional leaders. They calculate the returns on the political and economic investments made, which is not confined to a zero-sum game of winning elections. There are pay-offs even when one loses an election. Being in politics, a party activist has a distinct identity that could reap dividends in the form of prestige, status and accessibility. These could be converted to pecuniary benefits. Parties look like business firms in a political market. India having a population of a billion and a quarter and an electorate of 814 million (2014) - is the world’s largest democracy and this democratic system stands in marked contrast since independence.